AB1471-HPR The reliability and validity of a novel MRI-based tool for the evaluation of forefoot bursae in patients with rheumatoid arthritis: The "FFB-score". (23rd January 2014) - Hooper, L.; King, L.; Thomas, M.; Roemer, F.; Culliford, D.; Bowen, C.; Arden, N.K.; Edwards, C.J.
Abstract : Background: We recently demonstrated forefoot bursae (FFB) are a clinically important feature in patients with rheumatoid arthritis (RA) 1 . However, there is a need for an observer-independent, reliable and valid method of characterising FFB. Magnetic Resonance Imaging (MRI) allows improved visualisation and characterisation of FFB in multiple imaging planes. Objectives: To determine the reliability and validity of a novel MRI-based scoring tool for the evaluation of FFB in patients with RA. Methods: A collaborative process of tool design was completed by a team of rheumatologists, radiologists, and podiatrists from centres within the UK & Germany. In an iterative process of tool design, items to be included, grading criteria, overall utility and MRI sequences were determined. The FFB-Score assesses 9 distinct forefoot regions and contains 5 items; lesion presence, shape, enhancement and T1 & T2 characteristics. The final tool was evaluated on 42 consecutive patients with RA, mean(SD) age 62.2(±12) years, disease duration 15.3(±10.3) years, & DAS-28 3.1(±1.4), who were recruited from a UK rheumatology clinic. Images were obtained using a 1.5T whole body scanner and 4-channel flex extremity coil. The MRI protocol included coronal T1 & STIR, coronal & sagittal T1 post-gadolinium, and long axis 3D SPACE sequences. The intra and inter-reader reliability were evaluated using Percentage Exact/Close Agreement (PEA/PCA). Content validity was evaluated using Lawshes' Content Validity Ratio. Discriminant validity, with regards to differentiation between high/low clinical markers of disease activity (DAS-28), MRI-determined disease activity (erosion, bone marrow oedema, synovitis) or foot-related disability (Foot Impact Scale), was evaluated using receiver operator characteristic curves and area under the curve analysis. Results: The intra-reader reliability was determined as moderate for intermetatarsal soft tissue lesion shape (PEA:40% PCA:50%) and T1/T2 characteristics (PEA:60% PCA:90%, PEA:30% PCA:80% respectively) and good for all other items (PEA:50-90% PCA:100%). Inter-reader reliability was determined as good for all items (PEA:50-90% PCA:100%). Content validity was determined as good (Lawshes' CVR:0.625). The FFB-score total lesion enhancement grading has good discriminant validity when differentiating between patients with high/low MRI-determined disease activity in the forefoot (erosion:p=0.011, synovitis:p=0.004, oedema:p=0.018). The FFB-score has good discriminant validity for high/low reported foot impairment and activity limitation (p=0.006, p=0.033 respectively). Conclusions: The FFB-Score is a viable tool for the detection and evaluation of FFB in patients with RA, which demonstrates satisfactory intra/inter-reader agreement and validation. Further validation, assessment of responsiveness and refinement of the FFB-score is needed in order to maximize the potential utility in clinical trials and epidemiological studies. References: Bowen CJ et al. The clinical importance of ultrasound detectable forefoot bursae in rheumatoid arthritis. Rheumatol. (Ox.) 2010;59:1:191-2 Disclosure of Interest: None Declared